Nocardia colli sp. nov., a new pathogen isolated from a patient with primary cutaneous nocardiosis. Issue 5 (4th May 2020) - Zhou, Tao; Wang, Xiao-Yun; Deng, Dan-Qi; Xu, Li-Hua; Li, Xiao-Lan; Guo, Yun; Li, Wen-Hua; Xie, Hong; Zhang, Pei-Lian; Zhou, Xiao-Hong
Abstract : A novel nocardioform strain, CICC 11023 T, was isolated from a tissue biopsy of neck lesions of a patient with primary cutaneous nocardiosis and characterized to establish its taxonomic position. The morphological, biochemical, physiological and chemotaxonomic properties of strain CICC 11023 T were consistent with classification in the genus Nocardia . Whole-cell hydrolysates were rich in meso-diaminopimelic acid, galactose, arabinose and fructose. Mycolic acids were present. The major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, one unidentified phospholipid and two unidentified lipids, and the predominant menaquinone was cyclo MK-8 (H4, ω-cyclo). The main fatty acids (>5 %) were C18 : 0 10-methyl (TBSA), C16 : 0, summed feature 4 (C16 : 1 trans 9/C15 : 0 iso 2OH), C15 : 0 and C17 : 0 10-methyl. Phylogenetic analyses based on 16S rRNA gene sequences revealed that the isolate is most closely related (>98 % similarity) to the type strains Nocardia ninae OFN 02.72 T, Nocardia iowensis UI 122540 T and Nocardia alba YIM 30243 T, and phylogenetic analysis of gyrB gene sequences showed similarity (89.1–92.2 %) to Nocardia vulneris NBRC 108936 T, Nocardia brasiliensis IFM 0236 T and Nocardia exalbida IFM 0803 T . DNA–DNA hybridization results for strain CICC 11023 T compared to Nocardia type strains ranged from 20.4 to 35.4 %. The genome of strain CICC 11023 T was 8.78 Mbp with a G+C content of 67.4 mol% overall. The average nucleotide identity (ANI) values between strain CICC 11023 T and N. alba YIM 30243 T were low (OrthoANIu=77.47 %), and the ANI values between strain CICC 11023 T and N. vulneris NBRC 108936 T were low (OrthoANIu=83.75 %). Consequently, strain CICC 11023 T represents a novel Nocardia species on the basis of this polyphasic study, for which the name Nocardia colli sp. nov. is proposed. The type strain is CICC 11023 T (=KCTC 39837 T ).